A brief tour through the Wavelets - Ortiz Fernández, Alejandro (2022)
The objetive of these notes is to give a brief overview of wavelet theory, both of the fundamental mathematical arguments and of the ideas it contains. In addition, the theory is suitable for multidisciplinary work.